Hyaluronan Immobilized Polyurethane as a Blood Contacting Material - Feirong Gong; Yue Lu; Hui Guo; Shujun Cheng; Yun Gao (International Journal of Polymer Science)
Hyaluronan (hyaluronic acid, HA) was immobilized onto the surface of amino-functionalized polyurethane films with the goal of obtaining a novel kind of biomaterial which had the potential in blood-contacting applications. The amino-functionalized polyurethane was prepared by synthesized acidic polyurethane whose pendant carboxyl groups were treated with an excess amount of 1,3-diaminopropane in the presence of N,N-carbonyldiimidazole (CDI). Attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), Raman spectroscopy (RS), scanning electron microscopy (SEM), and water contact angle measurement were used to confirm the surface changes at each step of treatment, both in morphologies and chemical compositions. APTT and PT results showed that HA immobilization could prolong the blood coagulation time, thus HA-immobilized polyurethane (PU-HA) exhibited improved blood compatibility. Cytotoxicity analysis showed that the PU-HA films synthesized in this study were cytocompatible and could support human vein endothelial cells (HUVECs) adhesion and proliferation.